Чеклист флори околиць м. Балаклії (Харківська область, Україна): аборигенні та чужорідні таксони, поширення рідкісних рослин, нові знахідки - Shynder, Oleksandr; Negrash, Julia (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2021)
For the first time, information on the flora of the Siverskyi Donets basin in the vicinity of Balakliya town (Kharkiv region of Ukraine) was summarized based on the comprehensive analysis of published data, herbarium material, and own field examinations. Field surveys were conducted during September 2015 and March-July 2016. The surveyed areas were located mainly in the valleys of the Sіverskyi Donets river and some of its tributaries within the former Balakliуa district. The conspectus of flora comprising 933 taxa of vascular plants (including 798 recorded during field surveys) has been prepared. In particular, 739 taxa of native and 194 taxa of alien plants were recorded. The habitats of 14 species from the Red Book of Ukraine were found. The locations of other protected, uncommon and new for the flora of the region plant species were also identified. Several taxa (i.e., some of the calciphytes like Astragalus albicaulis, Linum czernjajevii, Odontarrhena tortuosa subsp. cretacea, Scutellaria supina, and Silene supina) were found out of their previously known ranges. Newly established locations of some other species (e.g., Ephedra distachya, Onosma simplicissima, and Ornithogalum boucheanum) significantly complement previously known chorological data. Finally, information about new findings of such alien taxa actively expanding new areas as Cornus sanguinea subsp. australis, Fraxinus pennsylvanica, Sedum sexangulare, Ulmus pumila, and Vitis vulpina is provided.It has been established that the flora of the Siverskyi Donets basin in the vicinity of Balakliya town is a rich natural center of phytodiversity being under active adventisation. Forest reclamation plantations play a significant role in spreading the alien plants. Railway and the pine terrace of the Siverskyi Donets also serve the migration corridors for many of such alien plants.